The Use of Core-Shell Nanoparticles in Photovoltaics - Alexander Quandt; Daniel Wamwangi; Sandile Kumalo (Photonics)
The field of photovoltaics (PV) continually seeks innovative materials solutions to enhance the efficiency and the stability of their standard devices. Core-shell nanoparticles have emerged as a promising new technology with unique structural attributes and widely tunable properties. This paper reviews the use of plasmonic core-shell nanoparticles in PV applications through various experimental validations. We describe advancements in the design and in the control over the properties of core-shell nanoparticles and highlight their integration into various solar cells, based on their ability to finely tune optical, electronic, and chemical properties. We also discuss experimental results for organic, perovskite, and dye-sensitized solar cells, where core-shell nanoparticles have been successfully deployed. Additionally, we identify gaps in the current research, such as the need for scalable synthesis methods and long-term stability assessments, and we will point out promising new developments at the frontier of that field.